Application of Genetics and Genomics in Poultry Science - Liu, Xiaojun (IntechOpen, 2018)
Genetics and genomics in poultry have been the most rapidly advancing subjects since the completion of the chicken genome sequence in 2004 and have been extensively used to understand the genetic determinants of complex traits. This book intends to provide readers with a comprehensive overview of the current progress in the application of genetic and genomic science in the poultry field. The contents cover genetic variation detection, selection methods for breeding, transgenesis and genome editing, genetic basis of disease resistance, control of gene expression and regulation, reproduction and meat quality, etc. The book should prove useful to researchers and students working in related fields.